Heavy Metals Accumulation in Sediment, Water and Various Tissues of Labeo Rohita in Papadi Lake of Vasai Taluka, Maharashtra - Pratik Pravin Kinare; Hitesh U. Shingadia (Journal of Indian Fisheries Association, 2023)
Heavy metal pollution is one of the rising concerns throughout the globe. Not only humans but also many other organisms have to suffer its consequences. Globally, fish consumption has been increased since the last century as fish provide an affordable and rich source of proteins, vitamins, and minerals. Rohu fish (Labeo rohita Hamilton, 1822) is one of the main commercial freshwater fish consumed in India. In the current study, heavy metals such as Arsenic, Cadmium, Chromium, Lead, and Mercury were considered for examination as these are amongst the most harmful metals for humans and other animals. Papadi Lake was one of the oldest lakes in Vasai Taluka, currently being used for cleaning activity, freshwater fish culturing and other daily chores by the local populace. Sediment, water and various organ tissues of Rohu fish such as gills, kidneys, liver and muscles were examined to find out the heavy metal accumulation. Seasonal variation was prominently observed in the accumulation of heavy metals in sediment, water, and all the fish tissues. The metal concentration in the lake was the result of the combined influence of natural and anthropogenic activities.